ALSUntangled #65: glucocorticoid corticosteroids. Issue 3 (3rd April 2023) - Goslinga, Jill Ann; Terrelonge, Mark; Bedlack, Richard; Barkhaus, Paul; Barnes, Benjamin; Bertorini, Tulio; Bromberg, Mark; Carter, Gregory; Chen, Amy; Crayle, Jesse; Dimachkie, Mazen; Jiang, Leanne; et al.
Abstract: ALSUntangled reviews alternative and off-label treatments for people with amyotrophic lateral sclerosis (PALS). Here we review glucocorticoids. Neuroinflammation plays a prominent role in amyotrophic lateral sclerosis (ALS) pathogenesis, so some hypothesize that glucocorticoids might be an effective ALS therapy through their immunosuppressive effects. In this paper, we review the available evidence for glucocorticoids in ALS, including one pre-clinical study with a genetic mouse model of ALS, nine case reports (ranging from 1 to 26 patients each), and four clinical trials. We also review the possible side effects (including steroid myopathy) and the costs of therapy. We graded the level of evidence as follows: Mechanism, D; Pre-Clinical, F; Cases, B; Trials, F; Risks, C. Our review of the current evidence concludes that glucocorticoids do not offer clinical benefit in ALS and confer serious risks. Thus, ALSUntangled does not recommend glucocorticoids as a treatment for ALS.